Technology aided learning application for wetlands ecology using constructivism approach - Ngwee, Jia Ler (2023)
Wetland Ecology Education delves into the intricate relationships between wetland ecosystems. Due to a lack of awareness of the need for their conservation, wetlands are now fragmented and subject to economic development. To ensure the long-term sustainability of these ecosystems, several researchers and educational institutions have developed environmental education initiatives. The project addresses the main challenges of contemporary education. Emphasis is placed on learning as a constructive process where students actively engage with information and connect it to existing knowledge. By integrating technology and constructivist principles, the project aims to create immersive and authentic learning experiences within learning applications. The system includes five different modules that enable users to understand wetland ecology from all aspects. The most important of these is the simulation module, which contains 3D virtual environments and 3D models, allowing users to gain immersive experience and interaction. There is also a section responsible for collecting user feedback. This project is mainly developed using unity. Other development tools include Blender, phpMyAdmin, and Figma. After the project development was completed, SUS testing and PPSUQ testing were also conducted to ensure the quality of the application. In short, this project must be a new breakthrough for wetland education and can greatly improve the understanding of wetland ecology.